Compensation Analysis on Employee Performance of CV. XYZ - Devi Havivah; Siti Mabrur Rachmah (Jurnal Ilmu Manajemen dan Ekonomika, 2024)
The company uses various ways to improve the performance of each of its employees, including education, training, compensation, creating a conducive and motivating work environment. Compensation is the right of employees and the obligation of the company to support the contribution of employees in order to achieve the goals that have been determined. Employee performance is one of the most important aspects in a company because it is one of the keys to the success of the company's targets. This type of research is descriptive with a non-statistical quantitative approach. The results of the study show that good performance is influenced by several factors. The factors that affect one of them are compensation. The provision of salaries, incentives and social security should be carried out according to employee performance to avoid unwanted things such as employee turnover.